Pengembangan Kompetensi Kepemimpinan Perawat Manajer Melalui Panduan Kompetensi - Ana Nurhani; Hanny Handiyani; Lilis Rayatin (Jurnal Keperawatan Silampari, 2022)
This study aims to develop the leadership competence of nurse managers through guidelines. The method used is a case study, using an action research approach. The results showed that the head of the room needed leadership competency development on average 42% strongly agreed, 58% agreed. Analysis of the problem of optimizing the manager's leadership competence with the development of a draft guide to the manager's leadership competence as a desire to implement leadership. Conclusions, support from required fields, and things that are needed to achieve the development of a nurse manager leadership competency guide draft. Keywords: Leadership Competence, Guide Development, Nurse Manager